Is lateral external perturbation training more beneficial for protective stepping responses than voluntary stepping training in stroke? A pilot randomized control study - Marcel B. Lanza; Masahiro Fujimoto; Larry Magder; Sandy McCombe-Waller; Mark W. Rogers; Vicki L. Gray (Journal of NeuroEngineering and Rehabilitation)
Abstract The study examined whether lateral perturbation training could improve stepping performance and balance in individuals post-stroke. Thirty-one participants with hemiparesis were randomly allocated to PERT (external perturbation) or VOL (voluntary stepping) step training. The PERT and VOL group consisted of 80 step trials predominantly in the lateral direction, with a small proportion of steps in the anterior/posterior direction. Outcome measures based on step type (medial and lateral) included step initiation time, step length, step clearance, step velocity during an induced waist pull perturbation and voluntary step, and clinical balance assessments. The PERT group initiated a lateral step faster with the non-paretic leg during the induced waist pull perturbation step (P = 0.044) than the VOL group after training. Both groups improved the non-paretic step length and step velocity during lateral steps. During the voluntary steps, the PERT group significantly initiated a voluntary step faster. No significant changes were observed in the paretic leg. Both groups significantly improved on the Community Balance & Mobility Scale and Activities Specific Balance Confidence Scale. Overall, we demonstrated that an exercise to improve stepping performance with external perturbations might provide more benefits in protective stepping responses than training with voluntary steps for individuals with a stroke.